Penanganan Arsip Dinamis Inaktif di Unit Kearsipan Dinas Prasarana Jalan, Tata Ruang, dan Pemukiman Provinsi Sumatera Barat - Mulyawati, Mita; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2013)
The purpose of this study was: (1) Describe the security records archival units inactivated in Road Infrastructure Agency, Spatial Planning and Housing of West Sumatra province, (2) to describe the obstacles encountered in securing the inactive records in archival units Agency Road Infrastructure, Spatial Planning and settlements of West Sumatra Province. This research includes descriptive research to obtain the necessary data in this study, the researchers conducted observations and interviews. The researchers conducted observations and interviews to two archivists. Safeguarding existing archives in archival unit has not been said to be good because there are no special security. Constraints faced by the archival unit in security for the archive (1) building frequent flooding archives so soak-arsp archive, which mostly comes from hard, (2) units kerasipan not have a special room, (3) do not create the archival unit order or regulation, (4) archivists do not have knowledge of the archives. Keywords: security records; inactive records